2019
DOI: 10.1096/fj.201802248r
|View full text |Cite
|
Sign up to set email alerts
|

The orphan nuclear receptor RORα is a potential endogenous protector in renal ischemia/ reperfusion injury

Abstract: Emerging evidence indicates that retinoid‐related orphan receptor (ROR)α, a member of the ROR nuclear receptor subfamily, mediates key cellular adaptions to hypoxia and contributes to the pathophysiology of many disease states. However, the effects of RORα in renal ischemia/reperfusion (I/R) injury remain unclear. Wild‐type (WT) C57 black 6 (C57BL/6) mice and RORα‐deficient stagger [ROR(sg/sg)] mice and their WT litter‐mates were used for in vivo studies. The renal I/R injury model was induced by bilateral ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The disruption of mitochondrial function and integrity caused by mitochondrial oxidative damage impacts redox signaling and oxidative stress and thereby induces necrosis and apoptosis. Mitochondrial oxidative damage participates in a wide range of pathologies, such as liver fibrosis [11], atherosclerosis [12], diabetes mellitus [13], and I/R injury in the intestine [[5], [6], [7]], kidney [14,15] and heart [16]. Accordingly, the scavenging of mitochondrial H 2 O 2 might be an important therapeutic measure for intestinal I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of mitochondrial function and integrity caused by mitochondrial oxidative damage impacts redox signaling and oxidative stress and thereby induces necrosis and apoptosis. Mitochondrial oxidative damage participates in a wide range of pathologies, such as liver fibrosis [11], atherosclerosis [12], diabetes mellitus [13], and I/R injury in the intestine [[5], [6], [7]], kidney [14,15] and heart [16]. Accordingly, the scavenging of mitochondrial H 2 O 2 might be an important therapeutic measure for intestinal I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…SR1078 was identified as the first synthetic RORα/γ agonist which modulated the conformation of RORγ and activates RORα‐ and RORγ‐driven transcription [25]. SR1078 has shown protective effects against a variety of diseases in mouse models, including autism [26], allergic asthma [27], liver cancer [28], liver fibrosis [29], renal ischaemia/reperfusion injury [30], rheumatoid arthritis [31], diabetic cardiomyopathy [32], neuroblastoma [21] and Machado‐Joseph disease [33]. Although SR1078 elicited such diverse benefits and effectively enhanced BMAL1 expression, SR1078 treatment failed to counteract cartilage degeneration in our study.…”
Section: Discussionmentioning
confidence: 99%
“…RORA plays a critical role in regulation of inflammation and its polymorphisms have recently been reported to have associations with susceptibility to migraine, pediatric asthma and multiple sclerosis [5][6][7]. A study by Cai and colleagues showed that RORA was downregulated in the kidney of mice after ischemia/reperfusion (I/R) injury and that a deficiency of RORA contributed to tubular epithelial cell apoptosis and consequently led to renal dysfunction [8], but the downstream targets of RORA in regulating renal cell apoptosis remained unclear.…”
Section: Introductionmentioning
confidence: 99%